Clitoria ternatea, The Alternative Shrub Legume for Cattle and Corn Integration System in Timor Island - Nulik, Jacob (Indonesian Bulletin of Animal and Veterinary Sciences, 2009)
Cattle and maize play important roles in the dryland faming systems in Timor island of East Nusa Tenggara province, contributing Â toÂ  the Â farmersâ Â income, Â social Â status, Â and Â the Â regional Â food Â security Â and Â sources Â of Â income. Â However, Â the productivity of both commodities is low because of several problems. Lack of feed supply and management knowledge has contributed to the low cattle productivity, while lack of cultivation knowledge and the use of low productivity local maize have caused low productivity in maize. Farmers in Timor in general do not apply fertilizer to their maize plants, although lack of nitrogen (N) is evident in many of their maize fields. There is potential to improve the available N in the soils through the incorporation of herbaceous legumes, which can supply the nutrient to the soil as well as providing good quality fodders for the cattle. Among the introduced herbaceous legumes tested, Clitoria ternatea (butterfly pea) has shown good performances to be used as an alternative herbaceous legume in the farming system for improving soil fertility and maize production as well as to provide good quality fordder for the cattle. Â  Key words: Crop Livestock System, herbaceous legumes, Clitoria ternatea, Timor, nitrogen fixation, maize